If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -2r = 15 Solving 9 + -2r = 15 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2r = 15 + -9 Combine like terms: 9 + -9 = 0 0 + -2r = 15 + -9 -2r = 15 + -9 Combine like terms: 15 + -9 = 6 -2r = 6 Divide each side by '-2'. r = -3 Simplifying r = -3
| x^2-34=-30 | | x^3-12x^2=0 | | x^2-34=30 | | 35x+43(4x+7)=9 | | -4=-1-3(2*-1+3) | | 8-8x=41-15x | | x-34=223333 | | (2x)/2=12 | | X+(x+5)+3(x+5)=420 | | y=5-3x | | 4.3=.4x | | 90*70= | | 3x+15=420 | | .666666667x+7=3 | | X^3-x+1=0 | | 5a-10b= | | .66666667x+7=3 | | (5y)3=45 | | 3+77= | | 3x-9x= | | (3x-7)(2x+5)=0 | | 2a+8c= | | 180=(10y)6 | | 10n+3=93 | | 5x^2+4=2(x+2) | | -21=x^2-12 | | 7a+14b= | | 6n+4=40 | | 3a^1b^3-6a^2b^2= | | 9a+12b= | | (x+5)(x-5)=-7 | | 2-8x=2x+9 |